Carbon fiber reinforced resin-based composite material based on sizing agent, preparation method and application

By sizing modification on the surface of the carbon fiber, the interface combination between the carbon fiber and the resin matrix is ​​optimized, and the problem of improving the balance between thermal conductivity and mechanical properties of composite materials is solved, and excellent thermal management and mechanical properties are achieved in high temperature environments.

CN119912813APending Publication Date: 2025-05-02SHANGHAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510278176.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The prior art is difficult to improve the overall strength and high temperature resistance of composite materials on the basis of ensuring thermal management performance, so as to achieve synchronous improvement and balance between thermal conductivity and mechanical properties.

Method used

The surface modification of carbon fiber is used to optimize the interface combination between carbon fiber and resin matrix. Through the coordination of the dual-carbon filler system and the sizing agent, the interface cross-linking gradient is regulated and the comprehensive performance of composite materials is improved.

Benefits of technology

The thermal conductivity and mechanical properties of composite materials are synchronously improved and balanced, especially in high temperature environments, showing excellent thermal management capabilities and tensile strength retention rates, meeting the needs of chip manufacturing and other industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912813A_ABST
    Figure CN119912813A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to a carbon fiber reinforced resin-based composite material based on a sizing agent, a preparation method and application. Wherein the carbon fiber reinforced resin-based composite material is prepared from a carbon filler, a resin matrix and a sizing agent, the carbon filler is a double-filler system formed by compounding carbon fibers and graphene, the resin matrix is a thermoplastic resin matrix, and the sizing agent is prepared from thermoplastic resin, a cross-linking agent, an organic solvent and deionized water; the sizing agent performs surface modification on the carbon fibers to enhance interface bonding between the carbon fibers and a resin matrix. According to the prepared composite material, by optimizing the interface transition gradient, good balance between the heat-conducting property and the mechanical property of the composite material is achieved, the tensile strength retention rate at 200 DEG C reaches 69%, meanwhile, the center temperature of electronic equipment is reduced to 30 DEG C, excellent heat management performance and mechanical strength are shown, and the composite material has good application prospects. The interface performance and the overall performance of the composite material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a sizing agent-based carbon fiber reinforced resin-based composite material, a preparation method and an application thereof. Background Art

[0002] Modern semiconductor technology is developing rapidly. The continuous expansion of chip area and power, including LED, has made the heat dissipation problem increasingly prominent. According to data from the International Semiconductor Industry Association, the increase in chip area is much faster than the increase in heat dissipation capacity, resulting in increased chip temperature, which in turn affects device performance and life. Therefore, thermal management materials have become one of the bottlenecks restricting the development of integrated circuit performance.

[0003] In the prior art, polyimide film, also known as PI film, is a new type of high-temperature resistant polymer film, which is made by drooling PAA solution into film and then imidizing it. PI film is amber in color, has excellent mechanical properties, dielectric properties, chemical stability, and high radiation resistance, corrosion resistance, high and low temperature resistance. It is one of the best super engineering polymer materials in the world and is known as the "golden film". It is one of the three bottleneck key polymer materials that restrict the development of high-tech industries in my country, along with carbon fiber and aramid fiber.

[0004] However, the performance potential of PI composites is still subject to certain limitations, especially the contradiction between thermal conductivity and mechanical properties. Although PI resin has a series of excellent properties, the interfacial bonding between it and the reinforcing filler is weak, which seriously affects the overall performance improvement of the composite material. Carbon fiber, as an excellent reinforcing material, has been widely used in composite materials. Its excellent mechanical properties and lightweight characteristics make it occupy an important position in high-strength and high-thermal conductivity composite materials. However, the hydrophilicity of the carbon fiber surface itself is poor, which makes the interfacial adhesion between it and the resin matrix weak, thus affecting the interfacial bonding and overall performance of the composite material. This interface problem often limits the dispersion of fillers and the comprehensive performance of composite materials in the traditional composite material production process.

[0005] However, due to various technical limitations, existing technologies are still unable to improve the overall strength and high temperature resistance of composite materials while ensuring thermal management performance, and to achieve simultaneous and balanced improvement of the thermal conductivity and mechanical properties of composite materials. Summary of the invention

[0006] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and to provide a carbon fiber reinforced resin-based composite material, a preparation method and an application thereof. The dual-carbon filler system is surface treated by sizing technology to optimize the interface bonding between the carbon fiber and the resin matrix, thereby improving the comprehensive performance of the composite material, especially the thermal management performance under high temperature environment, and achieving the simultaneous and balanced improvement of the thermal conductivity and mechanical properties of the composite material to meet the needs of industries such as chip manufacturing, thereby solving the above-mentioned technical problems.

[0007] In order to achieve the above object, the technical solution provided by the present invention is: A carbon fiber reinforced resin-based composite material based on a sizing agent, characterized in that: The composite material is prepared from carbon filler and resin matrix, wherein: Carbon filler is a dual filler system composed of carbon fiber and graphene, accounting for 15-25wt%; The resin matrix is ​​a thermoplastic resin matrix, accounting for 70-85wt%; The carbon fiber is surface-modified by a sizing agent to enhance the interface bonding between the carbon fiber and the resin matrix; The sizing agent is prepared from 3-10wt% of thermoplastic resin, 1-5wt% of cross-linking agent, 3-7wt% of organic solvent and 80-93wt% of deionized water.

[0008] The thermoplastic resin matrix, i.e., the precursor, includes: a mixture of one or more of hexafluoroisophthalic anhydride (6FDA), bisphenol A (BPA), phthalic anhydride (BTDA), 4,4'-diaminodiphenyl ether (ODA), 4,4'-diaminodiphenyl sulfone (DDS), dianhydride and diamine, and the monomer ratio is any one of 1:1, 1.05:1, 1.1:1, 1.15:1, 1:1.05, 1:1.1, and 1:1.15.

[0009] The compounding mass ratio of the carbon fiber and the graphene is 1:1, so that the interface constructed between the carbon filler and the resin matrix has a strengthened transition cross-linking gradient.

[0010] A method for preparing the sizing agent-based carbon fiber reinforced resin-based composite material, characterized in that the sizing agent is coated on the surface of the carbon fiber through a sizing process, a heat treatment is performed to promote the sizing agent to be fixed on the surface of the carbon fiber, and the sizing agent is chemically crosslinked and physically adsorbed during the processing of the composite material to form a stable interface; the carbon fiber reinforced resin-based composite material is obtained by adjusting the concentration of the sizing agent, regulating the amount of chemical crosslinking and physical adsorption between the sizing agent and the resin matrix, regulating the mutual diffusion ability between the sizing agent and the matrix, and regulating the thickness of the interface phase; When the filler ratio is fixed at 20wt%, the thermal conductivity and mechanical properties of the composite material can be adjusted simultaneously by regulating the concentration of the sizing agent and the ratio of the filler.

[0011] A sizing agent based carbon fiber reinforced resin matrix composite material for use in thermal management and electronic packaging.

[0012] Compared with the prior art, the present invention has the following obvious outstanding substantial features and significant advantages: 1. The carbon fiber reinforced resin-based composite material, preparation method and application provided by the present invention focus on achieving a balanced improvement in the thermal conductivity and mechanical properties of the composite material by optimizing the use of a dual filler system and a sizing agent. The present invention optimizes the surface properties of the carbon fiber by coating a suitable sizing agent on the surface of the carbon fiber, and adopts a physical adsorption and chemical cross-linking mechanism to enhance its interfacial adhesion with the polyimide matrix. The modification process improves the interfacial bonding force between the carbon fiber and the matrix resin, and also simultaneously improves the mechanical properties and thermal conductivity of the composite material.

[0013] 2. The present invention adopts a dual filler system of carbon fiber and graphene, and achieves an excellent balance between the thermal conductivity and mechanical properties of the composite material by adjusting the ratio and content of the two. The addition of graphene can effectively enhance the thermal conductivity of the material, while carbon fiber improves the mechanical strength of the composite material. The synergistic effect of the two significantly improves the thermal management and structural performance of the composite material.

[0014] 3. The present invention optimizes the formation of the interface crosslinking gradient in the composite material by precisely controlling the dosage of the sizing agent and the ratio of the filler, controls the interface bonding ability, and thus improves the thermal conductivity and mechanical properties of the composite material.

[0015] 4. The present invention exhibits excellent thermal management capabilities under high temperature conditions. In the composite material, at a filler content of 20 wt%, the temperature of the material is 13.7°C lower than that of the untreated material, and in an environment of 200°C, the tensile strength retention rate is as high as 69%, which greatly improves the comprehensive performance of the material.

[0016] 5. The composite material provided by the present invention is used for the heat dissipation components of electronic equipment, which can effectively reduce the temperature of the equipment and improve the heat dissipation efficiency. The LED temperature of the composite heat sink is 30°C lower than that of pure resin and 13.7°C lower than that of the unsizing composite material. It still has efficient heat dissipation capacity after multiple cycles of use. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 It is a schematic diagram of the microscopic morphology structure of the composite material before and after sizing modification according to an embodiment of the present invention.

[0018] Figure 2 It is a schematic diagram of the AFM modulation image and interface modulus distribution curve of the composite material before and after sizing modification in an embodiment of the present invention. DETAILED DESCRIPTION

[0019] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments so that those skilled in the art can implement the invention with reference to the description.

[0020] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0021] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0022] Basic Example

[0023] The carbon fiber reinforced resin-based composite material based on a sizing agent provided in this embodiment is prepared from a carbon filler and a resin matrix, wherein the carbon filler is a double filler system formed by compounding carbon fiber and graphene, accounting for 15-25wt%; The resin matrix is ​​a thermoplastic resin matrix, accounting for 70-85wt%; The sizing agent performs surface modification on the carbon fibers to obtain modified carbon fibers, so as to enhance the interface bonding between the carbon fibers and the resin matrix.

[0024] The sizing agent is prepared from 3-10wt% of thermoplastic resin, 1-5wt% of cross-linking agent, 3-7wt% of organic solvent and 80-93wt% of deionized water.

[0025] The thermoplastic resin matrix, i.e., the precursor, includes: a mixture of one or more of hexafluoroisophthalic anhydride (6FDA), bisphenol A (BPA), phthalic anhydride (BTDA), 4,4'-diaminodiphenyl ether (ODA), 4,4'-diaminodiphenyl sulfone (DDS), dianhydride and diamine, and the monomer ratio is any one of 1:1, 1.05:1, 1.1:1, 1.15:1, 1:1.05, 1:1.1, and 1:1.15.

[0026] The compounding mass ratio of the carbon fiber and the graphene is 1:1, so that the interface constructed between the carbon filler and the resin matrix has a strengthened transition cross-linking gradient.

[0027] A method for preparing the sizing agent-based carbon fiber reinforced resin-based composite material, which comprises the following steps: coating the sizing agent on the surface of carbon fibers through a sizing process, performing heat treatment to promote the sizing agent to be fixed on the surface of carbon fibers, and causing the sizing agent to undergo chemical crosslinking and physical adsorption during the processing of the composite material to form a stable interface; adjusting the concentration of the sizing agent, regulating the amount of chemical crosslinking and physical adsorption between the sizing agent and the resin matrix, regulating the mutual diffusion capacity between the sizing agent and the matrix, and regulating the thickness of the interface phase to obtain the carbon fiber reinforced resin-based composite material; and synchronously adjusting the thermal conductivity and mechanical properties of the composite material by regulating the concentration of the sizing agent and the proportion of the filler when the filler proportion is fixed at 20wt%.

[0028] The preparation method comprises the following steps: S1: The surface of the carbon fiber is cleaned with acetone and pre-oxidized with mixed acid, and then the treated carbon fiber is washed with deionized water until the pH value is 7, and then dried to obtain acidified carbon fiber; S2: dispersing a certain amount of acidified carbon fibers in the prepared graphene solution and stirring thoroughly to obtain a uniformly mixed carbon filler; S3: directly add deionized water to dilute the sizing agent so that its content is reduced from 8% to 1%, 2%, 3%, 4%, and 5% respectively; S4: soaking the carbon filler in the diluted sizing agent, and heating the temperature at 150° C., 200° C., and 250° C. respectively to obtain a sizing carbon filler; S5: treating the sized carbon filler with acetone reflux at 80°C for 12 h to prepare a desized carbon filler; S6: After the thermoplastic resin matrix and the carbon filler are fully mixed, hot pressing is performed at 420° C. and 20 MPa for 40 minutes to obtain a carbon fiber reinforced resin matrix composite material.

[0029] Furthermore, the step S6 is to obtain a thermoplastic polyimide composite material by fully mixing the thermoplastic polyimide matrix and the carbon filler and then hot pressing them.

[0030] A sizing agent based carbon fiber reinforced resin matrix composite material for use in thermal management and electronic packaging.

[0031] In order to optimize the interfacial bonding force between carbon fiber and resin matrix, the present invention adopts the surface modification technology of sizing, by coating a layer of appropriate sizing agent on the surface of carbon fiber, the wettability of carbon fiber and the bonding of resin can be effectively improved, thereby enhancing the interfacial adhesion, and then by means of chemical crosslinking and physical adsorption, the sizing agent is optimized to achieve better interface performance. In addition, the present invention adopts a double filler system as a thermal management material in a composite material, and the synergistic effect of two fillers can be brought into play, further improving the thermal conductivity and mechanical properties of the composite material. By accurately controlling the ratio of fillers, the mode of surface treatment and the amount of sizing agent, the overall strength and high temperature resistance of the material can be simultaneously improved while ensuring thermal management performance.

[0032] The present application will be further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then according to general international standards, normal conditions, or according to the conditions recommended by the manufacturer, proceed.

[0033] Example 1

[0034] The embodiment of the present invention is a specific application of the basic embodiment, and specifically provides a thermoplastic polyimide composite material of a modified carbon filler based on a sizing agent and a preparation method thereof.

[0035] A carbon fiber reinforced resin-based composite material based on a sizing agent, specifically a thermoplastic polyimide composite material, The composite material is prepared from carbon filler and resin matrix, wherein: The carbon filler is a dual filler system composed of carbon fiber and graphene in a ratio of 1:1, accounting for 22wt% (including 20wt% filler and 2wt% sizing agent); The resin matrix is ​​a thermoplastic polyimide resin matrix, accounting for 78wt%; The mass percentage of the sizing agent in the raw materials is 2wt%, and the sizing agent is specifically prepared from 8wt% of PMDA-ODA type polyimide, 5wt% of diaminodiphenyl sulfone, 7wt% of N,N-dimethylacetamide, and 80wt% of deionized water; A method for preparing a thermoplastic polyimide composite material based on a sizing agent comprises the following steps: S1: Take a certain mass of carbon fiber and use acetone solution to fully clean its surface to remove residual substances on the surface. After cleaning, put the carbon fiber into a mixed acid solution composed of sulfuric acid and nitric acid for pre-oxidation treatment, and repeatedly wash the treated carbon fiber with deionized water until the pH value of the solution reaches 7, and then dry it in a drying oven at 60°C to obtain acidified carbon fiber; S2: adding the acidified carbon fiber to the pre-prepared graphene solution and stirring at high speed on a magnetic stirrer to fully mix the carbon fiber and graphene to form a uniform carbon filler dispersion system. In this embodiment, the mass ratio of the acidified carbon fiber to the graphene is 1:1; S3: Pyromellitic anhydride (PMDA) and 4,4'-diaminodiphenyl ether (ODA) powders were placed in an oven to dry and remove excess water, and used as precursors to prepare thermoplastic polyimide solution. Under nitrogen atmosphere, ODA was dissolved in N,N-dimethylacetamide (DMAc), and after being completely dissolved, an ice water bath was added, and PMDA was added in small amounts several times, with a monomer ratio of 1:1. After adding a cross-linking agent, the mixture was reacted for 8 hours, and then diluted with deionized water to a concentration of 2% to obtain a thermoplastic polyimide sizing agent; S4: Soak the mixed carbon filler in the diluted sizing agent solution, so that the sizing agent can fully infiltrate and evenly cover the surface of the carbon filler. Then, the soaked carbon filler is subjected to heat treatment with different temperature gradients by using a programmed temperature increase method. The specific temperature increase steps are as follows: 150℃ for 1h, 200℃ for 1h, and 250℃ for 1h; S5: The thermoplastic polyimide resin is fully mixed with the desizing carbon filler, and a thermoplastic polyimide composite material PSGC-2 is prepared by a hot pressing process (420°C, 20MPa, 40min); S6: The prepared composite material needs to be tested for thermal conductivity and mechanical properties to verify the improvement of its comprehensive performance. This embodiment uses the following method for characterization: S6-1: Thermal conductivity test: A laser thermal conductivity meter was used to measure the thermal conductivity of the composite material. The film was used as a heat sink for high-power LED chips in actual high-temperature thermal management. An infrared camera recorded the temperature of the LED lamp to evaluate its thermal management capability. The thermal conductivity of the composite material was 11 W·m -1 ·K -1 , the center temperature of the LED is reduced by 30℃; S6-2: Mechanical properties test: DMA was used to test the tensile strength and Young's modulus of the composite material; the tensile strength was 73MPa and the Young's modulus was 2.7GPa; S6-3: Interface characterization: Use SEM to obtain the microscopic morphology of the material, and the characterization results of the control sample without sizing agent are as follows: Figure 1 As shown in the figure, after adding the sizing agent, the chemical crosslinking between the sizing agent and the carbon filler enhances the chemical adhesion, strengthens the interaction between the fillers, and makes the combination between the matrix and the fiber closer. The composite material is characterized by the atomic force microscope (AFM) mechanical mode to obtain the AFM modulation image and the interface modulus distribution curve. The interface modulus gradient change is controlled by adjusting the sizing agent concentration. Figure 2As shown in the figure, with the increase of sizing agent concentration, the interface thickness between the matrix and the fiber increases from 41nm without sizing agent to more than 100nm, which promotes the smooth transition of modulus and effective stress transfer. When the sizing agent concentration is too high, the interface thickness is too large, reaching 222.5nm, and the interface layer becomes too thick, which easily interrupts the heat conduction path. The thick and soft interface layer weakens the direct bond between the fiber and the matrix, resulting in a decrease in the stress transfer efficiency at the interface, resulting in stress concentration points, and then causing a decrease in the overall performance of the material. Example 2

[0036] The sizing agent-based thermoplastic polyimide composite material and the preparation method thereof provided in the embodiment of the present invention are substantially the same as those in Example 1, except that: The sizing agent-based thermoplastic polyimide composite material is prepared from a carbon filler and a resin matrix, wherein: The carbon filler is a dual filler system composed of carbon fiber and graphene in a 1:1 ratio, accounting for 20wt% (filler 19%, sizing agent 1%). The resin matrix is ​​a thermoplastic polyimide resin matrix, accounting for 80wt%; The preparation method thereof comprises the following steps: S1: Take a certain mass of carbon fiber and use acetone solution to fully clean its surface to remove residual substances on the surface. After cleaning, put the carbon fiber into a mixed acid solution composed of sulfuric acid and nitric acid for pre-oxidation treatment, and repeatedly wash the treated carbon fiber with deionized water until the pH value of the solution reaches 7, and then dry it in a drying oven at 60°C to obtain acidified carbon fiber; S2: adding the acidified carbon fiber to the pre-prepared graphene solution and stirring at high speed on a magnetic stirrer to fully mix the carbon fiber and graphene to form a uniform carbon filler dispersion system. In this embodiment, the mass ratio of the acidified carbon fiber to the graphene is 1:1; S3: The thermoplastic polyimide resin and the carbon filler are fully mixed, and a thermoplastic polyimide composite material PGC is prepared by a hot pressing process (420°C, 20MPa, 40min); S4: The prepared composite material needs to be tested for thermal conductivity and mechanical properties to verify the improvement of its comprehensive performance. This embodiment uses the following method for characterization: S4-1: Thermal conductivity test: A laser thermal conductivity meter was used to measure the thermal conductivity of the composite material. The film was used as a heat sink for high-power LED chips in actual high-temperature thermal management. An infrared camera recorded the temperature of the LED lamp to evaluate its thermal management capability. The thermal conductivity of the composite material was 5.6 W·m -1 ·K -1 , the center temperature of the LED is reduced by 14℃; S4-2: Mechanical properties test: DMA was used to test the tensile strength and Young's modulus of the composite material; the tensile strength was 57 MPa and the Young's modulus was 2.6 GPa; S4-3: Interface characterization: The composite material was characterized by using the atomic force microscope (AFM) mechanical mode to obtain the AFM modulation image and interface modulus distribution curve, and the SEM was used to obtain the material microscopic morphology image; Example 3

[0037] The thermoplastic polyimide composite material based on sizing agent and the preparation method thereof provided in the embodiment of the present invention are substantially the same as those in Example 1 and Example 2, except that: The sizing agent-based thermoplastic polyimide composite material is prepared from a carbon filler, a resin matrix and a sizing agent, wherein: The carbon filler is a dual filler system composed of carbon fiber and graphene in a ratio of 1:1, accounting for 25wt% (including 20% ​​filler and 5% sizing agent); The resin matrix is ​​a thermoplastic polyimide resin matrix, accounting for 75wt%; The sizing agent is prepared from 10 wt% of 6FDA-ODA thermoplastic polyimide resin, 5 wt% of diaminodiphenyl ether, 5 wt% of N,N-dimethylacetamide, and 80 wt% of deionized water; The preparation method of the thermoplastic polyimide composite material comprises the following steps: S1: Take a certain mass of carbon fiber and use acetone solution to fully clean its surface to remove residual substances on the surface. After cleaning, put the carbon fiber into a mixed acid solution composed of sulfuric acid and nitric acid for pre-oxidation treatment, and repeatedly wash the treated carbon fiber with deionized water until the pH value of the solution reaches 7, and then dry it in a drying oven at 60°C to obtain acidified carbon fiber; S2: adding the acidified carbon fiber to the pre-prepared graphene solution and stirring at high speed on a magnetic stirrer to fully mix the carbon fiber and graphene to form a uniform carbon filler dispersion system. In this embodiment, the mass ratio of the acidified carbon fiber to the graphene is 1:1; S3: Dry hexafluoroisophthalic anhydride (6FDA) and 4,4'-diaminodiphenyl ether (ODA) powders in an oven to remove excess water, and use them as precursors to prepare a thermoplastic polyimide solution. Under nitrogen atmosphere, ODA was dissolved in N,N-dimethylacetamide (DMAc), and after being completely dissolved, an ice water bath was added, and 6FDA was added in small amounts several times, with a monomer ratio of 1:1. After adding a cross-linking agent, the mixture was reacted for 8 hours, and then diluted with deionized water to a concentration of 5% to obtain a thermoplastic polyimide sizing agent; S4: Soak the above-mentioned uniformly dispersed carbon filler in the diluted sizing agent solution, so that the sizing agent can fully infiltrate and evenly cover the surface of the carbon filler. Then, the soaked carbon filler is subjected to heat treatment with different temperature gradients by a programmed temperature increase method, and the specific temperature increase steps are as follows: 150℃1h, 200℃1h, 250℃1h; S5: The thermoplastic polyimide resin and the desizing carbon filler were fully mixed, and a thermoplastic polyimide composite material PSGC-5 was prepared by a hot pressing process (420°C, 20MPa, 40min); S6: The prepared composite material needs to be tested for thermal conductivity and mechanical properties to verify the improvement of its comprehensive performance. This embodiment uses the following method for characterization: S6-1: Thermal conductivity test: The thermal conductivity of the composite material was measured using a laser thermal conductivity meter. The thermal conductivity of the composite material was 6.3 W·m -1 ·K -1 ; S6-2: Mechanical properties test: DMA was used to test the tensile strength and Young's modulus of the composite material; the tensile strength was 58MPa and the Young's modulus was 3GPa; S6-3: Interface characterization: The composites were characterized using the atomic force microscope (AFM) mechanical mode to obtain AFM modulation images and interface modulus distribution curves; Example 4

[0038] The thermoplastic polyimide composite material based on a sizing agent and the preparation method thereof provided in the embodiments of the present invention are substantially the same as those in Embodiments 1 to 3, except that: The sizing agent-based thermoplastic polyimide composite material is prepared from a carbon filler, a resin matrix and a sizing agent, wherein the carbon filler is a double filler system formed by compounding carbon fiber and graphene in a ratio of 1:1, accounting for 28wt% (including 22% filler and 3% sizing agent); The resin matrix is ​​a thermoplastic polyimide resin matrix, accounting for 72wt%; The sizing agent is prepared from 8 wt% of 6FDA-ODA thermoplastic polyimide resin, 5 wt% of diglycidyl ether, 7 wt% of N,N-dimethylacetamide, and 80 wt% of deionized water; The preparation method of the thermoplastic polyimide composite material comprises the following steps: S1: Take a certain mass of carbon fiber and use acetone solution to fully clean its surface to remove residual substances on the surface. After cleaning, put the carbon fiber into a mixed acid solution composed of sulfuric acid and nitric acid for pre-oxidation treatment, and repeatedly wash the treated carbon fiber with deionized water until the pH value of the solution reaches 7, and then dry it in a drying oven at 60°C to obtain acidified carbon fiber; S2: adding the acidified carbon fiber to the pre-prepared graphene solution and stirring at high speed on a magnetic stirrer to fully mix the carbon fiber and graphene to form a uniform carbon filler dispersion system. In this embodiment, the mass ratio of the acidified carbon fiber to the graphene is 1:1; S3: Dry hexafluoroisophthalic anhydride (6FDA) and 4,4'-diaminodiphenyl ether (ODA) powders in an oven to remove excess water, and use them as precursors to prepare a thermoplastic polyimide solution. Under nitrogen atmosphere, ODA was dissolved in N,N-dimethylacetamide (DMAc), and after being completely dissolved, an ice water bath was added, and 6FDA was added in small amounts several times, with a monomer ratio of 1:1. After adding a cross-linking agent, the mixture was reacted for 8 hours, and then diluted with deionized water to a concentration of 3%, to obtain a thermoplastic polyimide sizing agent; S4: Soak the above-mentioned uniformly dispersed carbon filler in the diluted sizing agent solution, so that the sizing agent can fully infiltrate and evenly cover the surface of the carbon filler. Then, the soaked carbon filler is subjected to heat treatment with different temperature gradients by a programmed temperature increase method, and the specific temperature increase steps are as follows: 150℃1h, 200℃1h, 250℃1h; S5: The thermoplastic polyimide resin and the desizing carbon filler were fully mixed, and a thermoplastic polyimide composite material PSGC-3 was prepared by a hot pressing process (420°C, 20MPa, 40min); S6: The prepared composite material needs to be tested for thermal conductivity and mechanical properties to verify the improvement of its comprehensive performance. This embodiment uses the following method for characterization: S6-1: Thermal conductivity test: The thermal conductivity of the composite material is measured using a laser thermal conductivity meter. The thermal conductivity of the composite material is 9W·m -1 ·K -1 ; S6-2: Mechanical properties test: DMA was used to test the tensile strength and Young's modulus of the composite material; the tensile strength was 68MPa and the Young's modulus was 2.9GPa; S6-3: Interface characterization: The composites were characterized using the atomic force microscope (AFM) mechanical mode to obtain AFM modulation images and interface modulus distribution curves; Example 5

[0039] The thermoplastic polyimide composite material based on sizing agent and the preparation method thereof provided in the embodiment of the present invention are substantially the same as those in Example 1 and Example 2, except that: The thermoplastic polyimide composite material is prepared from carbon filler and resin matrix, wherein: The carbon filler is a dual filler system composed of carbon fiber and graphene in a mass ratio of 1:2, accounting for 22wt% (including 20% ​​filler and 2% sizing agent); The resin matrix is ​​a thermoplastic polyimide resin matrix, accounting for 78wt%; The sizing agent is prepared from 8 wt% of BPA-ODA type thermoplastic polyimide resin, 5 wt% of triethylenetetramine (TETA), 7 wt% of N,N-dimethylformamide (DMF), and 80 wt% of deionized water; The preparation method of the thermoplastic polyimide composite material based on the sizing agent comprises the following steps: S1: Take a certain mass of carbon fiber and use acetone solution to fully clean its surface to remove residual substances on the surface. After cleaning, put the carbon fiber into a mixed acid solution composed of sulfuric acid and nitric acid for pre-oxidation treatment, and repeatedly wash the treated carbon fiber with deionized water until the pH value of the solution reaches 7, and then dry it in a drying oven at 60°C to obtain acidified carbon fiber; S2: adding the acidified carbon fiber to the pre-prepared graphene solution and stirring at high speed on a magnetic stirrer to fully mix the carbon fiber and graphene to form a uniform carbon filler dispersion system. In this embodiment, the mass ratio of the acidified carbon fiber to the graphene is 1:2; S3: Place bisphenol A (BPA) and 4,4'-diaminodiphenyl ether (ODA) powders in an oven to dry and remove excess water, and use them as precursors to prepare thermoplastic polyimide solution. Under nitrogen atmosphere, ODA was dissolved in N,N-dimethylformamide (DMF), and after being completely dissolved, an ice water bath was added, and BPA was added in small amounts several times, with a monomer ratio of 1:1. After adding a cross-linking agent, the mixture was reacted for 8 hours, and then diluted with deionized water to a concentration of 3%, to obtain a thermoplastic polyimide sizing agent; S4: Soak the above-mentioned uniformly dispersed carbon filler in the diluted sizing agent solution, so that the sizing agent can fully infiltrate and evenly cover the surface of the carbon filler. Then, the soaked carbon filler is subjected to heat treatment with different temperature gradients by a programmed temperature increase method, and the specific temperature increase steps are as follows: 150℃1h, 200℃1h, 250℃1h; S5: The thermoplastic polyimide resin was fully mixed with the desizing carbon filler, and a thermoplastic polyimide composite material PSG1C2-2 was prepared by hot pressing (420°C, 20MPa, 40min); S6: The prepared composite material needs to be tested for thermal conductivity and mechanical properties to verify the improvement of its comprehensive performance. This embodiment uses the following method for characterization: S6-1: Thermal conductivity test: The thermal conductivity of the composite material is measured using a laser thermal conductivity meter. The thermal conductivity of the composite material is 4 W·m -1 ·K -1 ; S6-2: Mechanical properties test: DMA was used to test the tensile strength and Young's modulus of the composite material; the tensile strength was 56 MPa and the Young's modulus was 2.5 GPa.

[0040] In the above embodiments of the present invention, by regulating the ratio of carbon fillers and the concentration of sizing agents, an interface transition gradient is formed between the carbon fillers and the resin matrix, the interface bonding of PSGC is enhanced, the modulus is smoothly transitioned and the stress is effectively transferred. After sizing at an appropriate concentration, there is no obvious separation or gap between the carbon fillers and the PI matrix. The present invention solves the problem of weak interfacial adhesion between carbon fiber and resin matrix in traditional composite materials by using sizing technology to modify the surface of the carbon filler, improves the interfacial properties of the composite material, and significantly improves the interfacial adhesion between the carbon fiber and the resin matrix. The chemical bonding force and physical adsorption between the carbon fiber and the thermoplastic polyimide matrix are enhanced. This improvement effectively improves the overall performance of the composite material, especially the performance in tensile strength and high temperature resistance is greatly improved, especially in high temperature environment, the tensile strength retention rate and Young's modulus of the composite material are effectively improved, and still maintains high mechanical properties under 200 ° C, meeting the high performance material requirements of industries such as aerospace and automobiles. At the same time, the thermal conductivity of the composite material is significantly improved. Especially in the application of heat dissipation and thermal management of electronic equipment, it has excellent thermal conductivity, which can effectively reduce the operating temperature of electronic equipment and extend the service life of the equipment.

[0041] In the above-mentioned embodiments of the present invention, the adjustment of the double filler system and the sizing agent makes the preparation of the composite material highly adjustable. According to different application requirements, the thermal conductivity, mechanical properties, interface bonding strength and other characteristics of the composite material can be flexibly adjusted by adjusting parameters such as filler ratio, sizing agent concentration, and processing temperature to meet the diverse needs of different fields for material properties. The preparation method of the present invention is relatively simple and scalable, suitable for large-scale industrial production. Due to the precise temperature control of the sizing process, controllable operation, and no need for overly complex equipment, the production cost is reduced and the production efficiency is improved. This makes the technology not only have high performance, but also possess high market competitiveness and have a wider application prospect.

[0042] In summary, the present invention provides a method for preparing a thermoplastic polyimide composite material by sizing modified carbon filler, which significantly improves the interfacial adhesion between carbon fiber and resin matrix through sizing modification technology, thereby improving the thermal conductivity and mechanical properties of the composite material. Specifically, the carbon fiber is first cleaned with acetone and pre-oxidized, and after being fully mixed with graphene, the carbon filler is surface treated with a sizing agent, and programmed temperature is increased at different temperatures. After sizing, it is fully mixed with a thermoplastic polyimide matrix and hot-pressed. Through this method, the tensile strength retention rate of the prepared composite material at 200°C reaches 69%, and the center temperature of the electronic device is reduced to 30°C, showing excellent thermal management performance and mechanical strength. The present invention provides a method of achieving a good balance between the thermal conductivity and mechanical properties of a composite material by optimizing the interface cross-linking gradient, providing an effective solution for optimizing the interface performance of the composite material, and providing theoretical guidance for optimizing the industrial sizing process, and providing a new research idea for improving the interface performance and overall performance of the composite material.

[0043] It should be particularly pointed out that within the scope of the components, proportions and process parameters recorded in the present invention, other technical solutions obtained by specific selection can achieve the technical effects of the present invention, so they are no longer listed one by one. Other technical solutions obtained by using components, proportions, preparation methods and applications equivalent to those recorded in the present invention are all included in the protection scope of the present invention.

[0044] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A carbon fiber reinforced resin-based composite material based on a sizing agent, characterized in that: The composite material is prepared from carbon filler and resin matrix, wherein: Carbon filler is a dual filler system composed of carbon fiber and graphene, accounting for 15-25wt%; The resin matrix is ​​a thermoplastic resin matrix, accounting for 70-85wt%; The carbon fiber is surface-modified with a sizing agent to enhance the interface bonding between the carbon fiber and the resin matrix; The sizing agent is prepared from 3-10wt% of thermoplastic resin, 1-5wt% of cross-linking agent, 3-7wt% of organic solvent and 80-93wt% of deionized water.

2. The carbon fiber reinforced resin-based composite material based on a sizing agent according to claim 1, characterized in that: The thermoplastic resin matrix, i.e., the precursor, includes: a mixture of one or more of hexafluoroisophthalic anhydride (6FDA), bisphenol A (BPA), phthalic anhydride (BTDA), 4,4'-diaminodiphenyl ether (ODA), 4,4'-diaminodiphenyl sulfone (DDS), dianhydride and diamine, and the monomer ratio is any one of 1:1, 1.05:1, 1.1:1, 1.15:1, 1:1.05, 1:1.1, and 1:1.

15.

3. The carbon fiber reinforced resin-based composite material based on a sizing agent according to claim 1, characterized in that: The compounding mass ratio of the carbon fiber and the graphene is 1:1, so that the interface constructed between the carbon filler and the resin matrix has a strengthened transition cross-linking gradient.

4. A method for preparing a carbon fiber reinforced resin-based composite material based on a sizing agent according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: coating a sizing agent on the surface of carbon fiber through a sizing process, performing heat treatment to promote the fixation of the sizing agent on the surface of carbon fiber, and causing the sizing agent to undergo chemical crosslinking and physical adsorption during the processing of the composite material to form a stable interface; and obtaining a carbon fiber reinforced resin-based composite material by adjusting the concentration of the sizing agent, regulating the amount of chemical crosslinking and physical adsorption between the sizing agent and the resin matrix, regulating the mutual diffusion ability between the sizing agent and the matrix, and regulating the thickness of the interface phase.

5. The preparation method according to claim 4, characterized in that It includes the following steps: When the filler ratio is fixed at 20wt%, the thermal conductivity and mechanical properties of the composite material can be adjusted simultaneously by regulating the concentration of the sizing agent and the proportion of the filler.

6. The preparation method according to claim 4, characterized in that It includes the following steps: S1: The surface of the carbon fiber is cleaned with acetone and pre-oxidized with mixed acid, and then the treated carbon fiber is washed with deionized water until the pH value is 7, and then dried to obtain acidified carbon fiber; S2: dispersing a certain amount of acidified carbon fibers in the prepared graphene solution and stirring thoroughly to obtain a uniformly mixed carbon filler; S3: directly add deionized water to dilute the sizing agent so that its content is reduced from 8% to 1%, 2%, 3%, 4%, and 5% respectively; S4: soaking the carbon filler in the diluted sizing agent, and heating the temperature at 150° C., 200° C., and 250° C. respectively to obtain a sizing carbon filler; S5: subjecting the sized carbon filler to acetone reflux treatment to prepare a desized carbon filler; S6: The thermoplastic resin matrix and the desized carbon filler are fully mixed, and then hot-pressed to obtain a carbon fiber reinforced resin matrix composite material.

7. The preparation method according to claim 6, characterized in that: In step S5, the sizing carbon filler is subjected to acetone reflux treatment at 80° C. for 12 h to prepare a desizing carbon filler.

8. The preparation method according to claim 6, characterized in that: The step S6 is to fully mix the thermoplastic resin matrix and the carbon filler, and then hot press them at 420° C. and 20 MPa for 40 minutes to obtain a carbon fiber reinforced resin matrix composite material.

9. The preparation method according to claim 8, characterized in that: The step S6 is to fully mix the thermoplastic polyimide matrix and the carbon filler and then hot-press them to obtain a thermoplastic polyimide composite material.

10. Use of the carbon fiber reinforced resin-based composite material based on the sizing agent according to any one of claims 1 to 3 in thermal management and electronic packaging.